Leisure, sport and tourism, politics, policy and planning - Veal, Anthony James, 1945- (CABI Tourism Texts, 2017)
A multi-disciplinary approach to policy making and planning in the leisure, sport and tourism sectors, this book provides an introduction for students. It examines theoretical issues underpinning public sector policy making, debates around the role of the state versus market, and models of organisational decision-making.